2019
DOI: 10.2147/vhrm.s191208
|View full text |Cite
|
Sign up to set email alerts
|

<p>Non-vitamin K oral anticoagulant use in the elderly: a prospective real-world study &ndash; data from the REGIstry of patients on Non-vitamin K oral Anticoagulants (REGINA)</p>

Abstract: Purpose Numerous studies on thromboembolic prevention for non-valvular atrial fibrillation (NVAF) have shown either equal or better efficacy and safety of non-vitamin K oral anticoagulants (NOACs) compared to warfarin, even for patients aged ≥75 years. Data on elderly patients, in particular, octogenarians, are lacking. Paradoxically, this population is the one with the highest risk of bleeding and stroke with a worse prognosis. This study aims to describe safety and effectiveness of NOACs in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
(37 reference statements)
6
20
0
4
Order By: Relevance
“…The present study had a non-inferior safety and efficacy outcome while on the OAC treatment compared to the real-world studies that included patients older than 65 years. 11,12 Our data revealed that the OAC treatment was safe and effective for the management of AF in octogenarians if their frailty was not so severe. Note: Data are expressed as the number (incidence rates).…”
Section: Assessment Of the Safety And Efficacy Outcomementioning
confidence: 73%
“…The present study had a non-inferior safety and efficacy outcome while on the OAC treatment compared to the real-world studies that included patients older than 65 years. 11,12 Our data revealed that the OAC treatment was safe and effective for the management of AF in octogenarians if their frailty was not so severe. Note: Data are expressed as the number (incidence rates).…”
Section: Assessment Of the Safety And Efficacy Outcomementioning
confidence: 73%
“…Группы в исследовании были практически идентичны по своим клиническим и анамнестическим характеристикам, что внушает доверие к полученным результатам. Данные регистра REGINA [9]в значительной степени идентичны нашим: группы были однородны по своей структуре, единственным значимым различием был возраст (как и в нашем исследовании, самыми возрастными оказались пациенты, включенные в группу апиксабана). Пациенты в обоих исследованиях демонстрировали высокий риск тромботических осложнений по шкале CHA 2 DS 2 -VASc.…”
Section: Discussionunclassified
“…Об этом свидетельствуют результаты самых крупных исследований [4][5][6] и данные реальной клинической практики [7,8]. Единственным исследованием, в котором проведено прямое сравнение ПОАК между собой, стал недавно опубликованный регистр REGINA: сравнивались пациенты с ФП в возрасте ≥67 лет, принимающие дабигатран, апиксабан и ривароксабан в соответствующих дозировках [9].…”
Section: Comparison Of Noacs In Patients Over 75 Years Oldunclassified
“…44,45 Newer agents such as the direct oral anticoagulants (DOACs) are now considered the preferred option demonstrating similar efficacy in preventing stroke and systemic embolism, with a lower risk of major bleeding compared to warfarin. 46 Warfarin also seems to be associated with increased risk of osteoporotic fractures compared to the DOACs. 47 All DOACs require dose adjustments for renal function.…”
Section: Arrhythmias Atrial Fibrillationmentioning
confidence: 99%